A General Decision Model for Cost-Volume-Profit Analysis under Uncertainty. - Shih, Wei (The Accounting Review, 1979)
ABSTRACT: This paper presents a general decision model for cost-volume-profit (C-V-P) analysis which takes into account the crucial elements of random demand and level of production in the determination of actual sales and resulting pro purpose of the model construction offered here is to invest C-V-P analysis with realism, and to remove a basic deficiency from the traditional C-V-P model. The general model enables the management to choose the pest among alternative products, and to determine, concurrently, optimal production levels in the light of a firm's goals and objectives. Various measures of uncertainty with regard to the behavior of the profit are developed, and their applications are illustrated in numerical examples. Two FORTRAN programs are also supplied to facilitate computation.